Deconstruction thought in image of Islam architecture - Ibrahim Jawad Kadhim (Iraqi Journal of Architecture and Planning, 2018)
Prepare architecture, Pot to the creative and aesthetic situations of man, Carrying features consistent with the needs of man, and in accordance with his traditions and environment, Characterized by the absorption of several aspects to grow While ,for the thought of deconstruction, the most important part of dealing with theinvestment of architectural ideas in forms approved by it or the texts presented therein, to create configurations relied upon. In addition, the research interest in "generating design ideas between the search for strange forms and other forms of architecture, Arab or local to form forms desirable and non expendable." This is what determined the problem of research in explaining the impact of the thought of deconstruction in building images of the architecture of Islam. In addition, When we look at deconstruction as a curriculum of Islamic knowledge, the study of an idea is worthy of study and reflection especially in an era dominance Western knowledge and sovereignty outside its environment. In addition, the research concluded that the image of Islamic architecture gave the fixed meaning and its foundation to the twosituations of complete disagreement over everything that preceded it and correlative symmetry in many self-characteristics a place. While the forms of thought reflective based on the case of cross-differencein a few characteristics of the previous (the other is images architecture of Islam) time and the similar damage to the participation in a few characteristics of a place gave the change in shape.